2013
DOI: 10.1002/pola.26855
|View full text |Cite
|
Sign up to set email alerts
|

Soluble and transparent polyimides from unsymmetrical diamine containing two trifluoromethyl groups

Abstract: A new unsymmetrical diamine monomer containing two trifluoromethyl (CF 3 ) groups is prepared from 2-bromo-5nitro-1,3-bis(trifluoromethyl)benzene. The monomer is polymerized with typical dianhydrides, in this case PMDA, BPDA, BTDA, ODPA, and 6-FDA, using a one-pot synthetic method to obtain corresponding polyimides. All of the prepared polyimides are readily soluble in many organic solvents and can be solution-cast into transparent, flexible, and tough films. These films have a UV-vis absorption cut-off wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 37 publications
0
62
0
Order By: Relevance
“…Kim et al. designed and synthesized an unsymmetrical –CF 3 substituted diamine monomer, 4‐(4 ′ ‐aminophenoxy)‐3,5‐bis(trifluoromethyl)aniline (3), following a two‐step methodology, as shown in Scheme . Nucleophilic aromatic substitution reaction (SNAr) of 2‐bromo‐5‐nitro‐1,3 bis(trifluoromethyl)benzene (1) with 4‐nitrophenol in the presence of K 2 CO 3 produced the dinitro compound (2) which on subsequent reduction by H 2 in the presence of Pd/C catalyst delivered the desired diamine 3.…”
Section: Recent Design Approaches To Prepare Cpismentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al. designed and synthesized an unsymmetrical –CF 3 substituted diamine monomer, 4‐(4 ′ ‐aminophenoxy)‐3,5‐bis(trifluoromethyl)aniline (3), following a two‐step methodology, as shown in Scheme . Nucleophilic aromatic substitution reaction (SNAr) of 2‐bromo‐5‐nitro‐1,3 bis(trifluoromethyl)benzene (1) with 4‐nitrophenol in the presence of K 2 CO 3 produced the dinitro compound (2) which on subsequent reduction by H 2 in the presence of Pd/C catalyst delivered the desired diamine 3.…”
Section: Recent Design Approaches To Prepare Cpismentioning
confidence: 99%
“…Synthesis of the unsymmetrical diamine monomer. Reproduced with permission . Copyright 2013, John Wiley & Sons, Inc.…”
Section: Recent Design Approaches To Prepare Cpismentioning
confidence: 99%
“…Most of these approaches to obtain soluble polymers were aimed at reduction of several types of chain-chain interactions, such as chain packing (e.g., crystallinity), charge transfer, and electronic polarization interaction. Polyimides, containing structurally asymmetric diamine monomers that contain flexible ether linkages [17] or bulky trifluoromethyl [18,19] substituent groups showed enhanced solubility behavior. Our research group has also previously reported the preparation of fluorinated PAIs [20] and poly(amide-imide)s-poly(amide imide) composite membranes by interfacial polymerization technique.…”
Section: Introductionmentioning
confidence: 98%
“…To overcome these problems of PIs, many effort has been focused on synthesis of Low-k and colorless PIs, without deterioration of the resulting PIs [16e20]. There are several approaches to prepare colorless PIs, including the introduction of flexible and unsymmetrical linkages or noncoplanar monomers and bulky or fluoro-containing substituents [21,22]. Fluorination is one of the most widely used methods to reduce the dielectric constant while lowering moisture absorption and improving solubility and optical properties [23e26].…”
Section: Introductionmentioning
confidence: 99%